Correlation Between MMSE Scores and NIHSS In Acute Stroke Infarct Patients - Fikriyah, Lathifatul (Riviera Publishing, 2025)
Stroke is defined as an episode of neurological dysfunction resulting from focal infarction of the brain, spinal cord, or retina, confirmed by pathological findings, imaging, or other objective evidence of ischemia within a specific vascular territory. Alternatively, stroke may be diagnosed based on the presence of clinical symptoms persisting for ?24 hours or resulting in death, provided other potential causes have been excluded. Stroke patients may experience cognitive, sensory, and motor dysfunction as a result of brain cell damage, which can affect their ability to communicate and carry out daily tasks. Objective: To ascertain the correlation between acute infarction stroke patients' cognitive performance and stroke severity at Dr. Sutomo Surabaya Hospital Methods: An analytical observational cross-sectional design was used in this investigation. Patients diagnosed with acute ischemic stroke who were admitted to Dr. Soetomo Surabaya Hospital between February and May 2023 and who satisfied the inclusion and exclusion criteria made up the study population. A consecutive admission strategy was used for sampling. Serum lactate dehydrogenase (LDH) levels and the National Institutes of Health Stroke Scale (NIHSS) score were evaluated upon admission. Results: The study included 30 patients in all, 14 (46.7%) female and 16 (53.3%) male. There is a correlation between MMSE and NIHSS, according to statistical tests that deem these results significant. The table's results for the correlation test between MMSE and NIHSS Score using the Pearson test show that the p-value is 0.000, where the value is < 0.05. The correlation test's r value is 0.905, meaning that the degree of association between the MMSE score variable and NIHSS is 0.905, or 90.5%, and that the value falls into the strong relationship strength category. The MMSE and NIHSS scores have a negative association; a high or big MMSE score will result in a low NIHSS score, and vice versa. Conclusion: There is a strong negative correlation between MMSE score and functional level assessed by NIHSS in patients with acute ischemic stroke, and statistically significant.